Melagatran, a Low Molecular Weight Thrombin Inhibitor, Counteracts Endotoxin-induced Haemodynamic and Renal Dysfunctions in the Pig - Eriksson, Mats; Larsson, Anders; Saldeen, Tom; Mattsson, Christer (Thrombosis and Haemostasis, 1998)
Coagulation and fibrinolysis are crucial in septic shock and inhibition of thrombin may be beneficial in this circumstance. Since porcine endotoxaemia has been found to replicate severe septic shock, a low molecular weight thrombin inhibitor, melagatran, was infused during the first 3 out of 6 h of endotoxaemia in pigs. Plasma creatinine (p <0.01) and urinary output (p <0.05) were less affected in the melagatran + endotoxin group (n = 6) as compared to endotoxaemic controls (n = 9). The left ventricular stroke work index, systemic vascular resistance index and oxygen extraction were all less affected (p <0.05) by endotoxin during the infusion of melagatran. The plasma concentration of melagatran declined with an apparent plasma half-life of 5 h as soon as the infusion was stopped. APTT, however, continued to increase after the infusion of melagatran had stopped and reached a maximum of 113 s at 5 h (baseline 17 s). APTT in endotoxaemic control pigs reached a maximum of 22 s. Thus, melagatran may counteract some consequences of endotoxaemia.